Kekuatan Hukum Penyelesaian Sengketa Waris Melalui Mediator Tokoh Masyarakat di Desa Wonosalam Kecamatan Wonosalam Kabupaten Demak - Ahmad Falih Mahrus (AL-HUKAMA, 2019)
This article is a field research to answer the role of community leaders as mediators in the settlement of inheritance disputes in Wonosalam, Demak and how the legal power of resolving inheritance disputes through mediator community leaders in Wonosalam, Demak. Research data are collected through interviews and observations, then are analyzed with descriptive analytical techniques with inductive thought pattern. Wonosalam community leaders have an important role in the settlement of inheritance disputes, namely as a mediator, including: opening and leading the mediation process, explaining and determining the heirs' parts, providing the best advice and solutions, deciding and determining what has been agreed by the parties to the dispute, preventing the emergence of even bigger disputes, and still maintaining harmony and harmony in social life. The results of the settlement of inheritance disputes through mediators of community leaders in Wonosalam do not have an enforceable legal force, because they are not confirmed by making a peace certificate or a peace agreement letter, which is contained in: article 27 of the Supreme Court Regulation No. 1 of 2016 concerning Mediation Procedures and article 1851 Civil Code. Nevertheless, the determination of community leaders as mediators in the settlement of inheritance disputes is obeyed and implemented by the people of Wonosalam.